Prevalence of enteropathogens of zoonoticsignificance in fish and fish products fromLudhiana - Sharma, C S; Bedi, S K; Gill, J P S; Aulakh, R S; Sharma, J K (Indian Journal of Fisheries, 2014)
Bacteriological examination of 23 raw fresh water fish and 8 fish pakoda samplesrevealed incidence of Escherichia coli, Salmonella, Klebsiella pneumoniae,Proteus mirabilis, Proteus vulgaris, Enterobacter aerogenes, Enterobacteragglomerans and unidentified gram negative bacilli in 9.6, 3.2, 19.3, 6.4, 6.4,9.6, 3.2 and 9.6% samples, respectively. Three E. coli isolates belonging toserotypes O: 8 (2) and O: 106 (1) were detected and the only Salmonella isolatewas serotyped as Salmonella typhimurium. All the 21 isolates of variousenteropathogens were tested for enterotoxigenicity by rabbit illeal loop methodand skin permeability factor assay, which demonstrated that 38.0% of the isolateswere enterotoxigenic. Enterotoxigenic response observed in S. typhimurium, E.coli, K. pneumoniae and P. mirabilis was 100.0, 66.6, 66.6 and 50.0 per cent,respectively. Majority of these bacteria are important from human health pointof view due to their pathogenicity and direct association with the onset of diarrhea in man.